2016
DOI: 10.1177/0887403416638507
|View full text |Cite
|
Sign up to set email alerts
|

Developing Empirically Informed Policies for Sexual Assault Kit DNA Testing: Is It Too Late to Test Kits Beyond the Statute of Limitations?

Abstract: A growing body of research indicates that there are thousands of sexual assault kits (SAKs) in police property storage facilities that have never been submitted for DNA forensic testing. Some of these rape kits may be quite dated, and the statute of limitations (SOL) for prosecution of the case may have expired. Whether testing such kits could still provide useful information for criminal justice system personnel is unknown. To address this gap in the literature and to inform policy regarding rape kit testing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…The argument in favor of prioritization on these grounds is that the probative value of forensic results is higher in cases in which the victim and offender are strangers because in those incidents of sexual assault, DNA testing and a possible CODIS match may offer the best chance to identify a suspect and solve the case (Johnson et al, 2012;Peterson et al, 2012). Others, however, have challenged the idea that prioritizing is a viable approach to testing based on evidence that DNA CODIS suspect matches are equally likely to come from cases involving strangers as those in which the victim and offender knew each other (R. Campbell et al, 2019;Lovell et al, 2018).…”
Section: Probative Value and The Decision To Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The argument in favor of prioritization on these grounds is that the probative value of forensic results is higher in cases in which the victim and offender are strangers because in those incidents of sexual assault, DNA testing and a possible CODIS match may offer the best chance to identify a suspect and solve the case (Johnson et al, 2012;Peterson et al, 2012). Others, however, have challenged the idea that prioritizing is a viable approach to testing based on evidence that DNA CODIS suspect matches are equally likely to come from cases involving strangers as those in which the victim and offender knew each other (R. Campbell et al, 2019;Lovell et al, 2018).…”
Section: Probative Value and The Decision To Testmentioning
confidence: 99%
“…Comprehensive testing and submission of DNA profiles is also important for the identification of serial offenders. Evidence suggests that most offenders commit more than one sexual offense (Lisak & Miller, 2002) and analysis of SAKs has underscored these findings (R. Campbell et al, 2019;Lovell et al, 2017). Accordingly, even if the statute of limitations has passed, there remains value in testing previously untested kits (R. Campbell et al, 2019).…”
Section: Test All Mandatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the potential value of testing SAKs is plentiful. The testing of kits—regardless of victim-offender relationship and statute of limitations—can result in CODIS hits (Campbell et al, 2016; Campbell et al, 2018; Campbell et al, 2019b) and help identify previously unknown suspects, confirm identities of identified suspects, and exonerate those who have been wrongfully convicted (Campbell et al, 2017a). Recently, researchers have explored how the testing of previously unsubmitted kits can help identify serial sex offenders (Campbell et al, 2019a; Campbell et al, 2020; Lovell et al, 2019; Lovell et al, 2020).…”
Section: Sexual Assault Kitsmentioning
confidence: 99%
“…Campbell, Feeney, et al, 2016; R. Campbell, Pierce, Sharma, Feeney, & Fehler-Cabral, 2016b; see also Spohn, 2016; Wells, 2016), as well as kits involving cases both within and outside of the statute of limitations (R. Campbell, Pierce, Sharma, Feeney, & Fehler-Cabral, 2016a).…”
Section: Sexual Assault Kits and The Criminal Justice Systemmentioning
confidence: 99%